Prevalence of dental caries among male students aged 15–17 years in southern Asir, Saudi Arabia - Ibrahim Alshahrani; Shreyas Tikare; Zakirulla Meer; Abdelbagi Mustafa; Mohammed Abdulwahab; Syed Sadatullah (Saudi Dental Journal)
Background: Dental caries had been studied by several studies in Saudi Arabia among different age groups and at various places. According to World Health Organization (WHO), assessment of caries at 15 years of age is more meaningful. The objective of this survey was to assess the prevalence of dental caries among 15–17-year teenage students in Abha, Saudi Arabia. Results of the present study can be used as baseline data for future oral health interventions for the population. Methods: A stratified cluster random sampling was followed in selecting the students. The clinical data was collected using dentition status component of WHO oral health assessment form 2013. Five investigators were trained and calibrated with 20 subjects for two successive days (Cronbach's Alpha = 0.91). Data was analyzed for descriptive statistics and Mann-Whitney U test was applied to compare the DMFT scores. Results: Prevalence of dental caries among the study population was found to be 72.9%. The DMFT scores were found to be highest in the posteriors (90.7%). First permanent molar was the most common tooth affected by dental caries in all quadrants. Conclusion: The present study revealed that there is a high prevalence of dental caries among students aged 15–17 years in Abha, Saudi Arabia. Caries prevalence was highest in mandibular posterior segments, however, it was lowest in mandibular anterior segments. There is an urgent need for both preventive and curative dental health services in the region. It is recommended that a coordinated school dental program may be initiated in the area. Keywords: Adolescent, Dental caries, Epidemiology, Prevalence